(untitled) (Proceeding of SINERGY, 2026)
The manufacturing sector in Indonesia plays a crucial dualistic role: as the backbone of national economic growth with a significant contribution to GDP, but also as a major contributor to environmental degradation thru greenhouse gas emissions and industrial waste. Faced with this paradox, companies are required to undergo a sustainability transformation that is not only technical but also cultural. This research aims to map and synthesize current literature on the integration of Green Human Resource Management (GHRM) and Green Supply Chain Management (GSCM) as key determinants of Sustainable Performance. Using the Systematic Literature Review (SLR) method with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, this study examined relevant empirical articles to identify relationship mechanisms, methodological trends, and research gaps. The review results indicate that GHRM serves as a foundation for building employes’ green capabilities and culture, which is then operationalized thru GSCM practices to achieve holistic sustainability performance. This article makes a theoretical contribution by clarifying the role of GSCM mediation within the Ability-Motivation-Opportunity (AMO) framework and offers a framework for industry managers to align HR policies with operational strategies.